Public-Private Partnerships (PPPs): Potential Impacts and Critical Success Factors - Nasios, Georgios; Foradoula, Niki (HAPSc Policy Briefs Series, 2021)
In recent years, PPPs have been increasingly used to implement projects and provide public services. The governments have made the necessary legislative and financial efforts in order to promote PPPs, given the need to acquire know-how from the private sector and the advantages they bring to the public sector and the citizens. However, the use of PPPs should be carefully planned as, in addition to the wider social and economic impacts, failures and negative results have been observed. This article attempts to present the main characteristics of PPPs, cite their possible impacts and quote their critical success factors in order to make PPPs more beneficial for the involved parties and the citizens.